Transforming Business School Futures: Business Model Innovation and the Continued Search for Academic Legitimacy - THOMAS, Howard (Institutional Knowledge at Singapore Management University, 2014)
The business school is certainly one of the major success stories in higher education over the last 40 years. Despite this success there have been many more recent comments and criticisms and about the purpose, role and academic stature of business schools. Thomas et al. (2013, pp. 8-9) outline thoroughly the nature of these criticisms in the following manner: “Critics accuse business schools of doing arcane, irrelevant and impractical academic research; doing a poor job of preparing students for management careers; pandering to the market and the media rankings; failing to ask important questions; and in the process of responding to the demands from their environment, losing claims of professionalisation as they ‘dumb down’ the content of courses, inflate grades to keep students happy, and pursue curricular fads”. Others argue that contemporary management education does a disservice to the profession by standardizing content, being too analytical and not action oriented, focusing on business functions (instead of the process of managing) and training specialists (rather than general managers). Indeed, they point out that educators do not appear to recognise that management is an art and not a science (Mintzberg, 2004). They also criticise business schools for being too insular and not global in their thinking and values, and for not fully integrating experience, theory and reflection into group (rather than individual) decision-making processes. And, these critics perceive that business schools do not encourage managers to incorporate an integrative, team-based philosophy and do not provide sufficient ethical and professional guidance.